2018
DOI: 10.1016/j.urolonc.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of large renal masses followed on observation

Abstract: In highly comorbid patients, the observation of large renal masses has low likelihood for metastatic progression relative to the risk of nonkidney cancer related death. This data supports the use of surveillance as an acceptable strategy for highly selected patients with competing risks from other serious illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…[7][8][9]25 or focus on poor surgical candidates undergoing observation of large renal masses. [10][11][12][13][14] Similar to our results, Mano et al retrospectively reviewed 1,278 patients at a single center and found that increasing surgical delay for renal masses >4 cm (median tumor size, 6.2 cm) was significantly associated with decreased OS after adjusting for patient and tumor characteristics. 8 Interestingly, these investigators did not find surgical delay to be associated with tumor upstaging, recurrence, or cancer-specific survival.…”
Section: Commentsupporting
confidence: 86%
See 3 more Smart Citations
“…[7][8][9]25 or focus on poor surgical candidates undergoing observation of large renal masses. [10][11][12][13][14] Similar to our results, Mano et al retrospectively reviewed 1,278 patients at a single center and found that increasing surgical delay for renal masses >4 cm (median tumor size, 6.2 cm) was significantly associated with decreased OS after adjusting for patient and tumor characteristics. 8 Interestingly, these investigators did not find surgical delay to be associated with tumor upstaging, recurrence, or cancer-specific survival.…”
Section: Commentsupporting
confidence: 86%
“…The literature is limited in addressing the association surgical delay with oncologic outcomes in patients with large renal masses. Published reports largely consist of retrospective single institution studies 7 , 8 , 9 , 25 or focus on poor surgical candidates undergoing observation of large renal masses 10 , 11 , 12 , 13 , 14 . Similar to our results, Mano et al retrospectively reviewed 1,278 patients at a single center and found that increasing surgical delay for renal mass >4 cm (median tumor size, 6.2cm) was significantly associated with decreased OS after adjusting for patient and tumor characteristics 8 .…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…A separate study detailing the natural history of untreated cT1b tumors found that lesions which progressed to metastasis had a linear growth of 0.9 cm/year compared to 0.67 cm/year for tumors that eventually remained stable 55 . With pandemic limitation in access to elective surgical care, the data indicate that an initial short period of surveillance, with interval imaging at 3‐6 months, is safe 56 and would permit an understanding of tumor growth kinetics so as to allow proper triaging of patients with respect to need for immediate vs deferred intervention.…”
Section: Evidence For Safety Of Delayed Surgerymentioning
confidence: 99%